Assessment of science teachers’ awareness and perception of analogy use in Ilorin, Nigeria - Odeniyi, Oluwasegun Olawale; Mohammed, Ridwan Enuwa (Penerbit Universiti Kebangsaan Malaysia, 2023)
Analogies are useful tools for teaching difficult scientific concepts and clearing learners’ misconceptions. However, when teachers do not properly perceive analogies, they will be misused, leading to further misconceptions. This study assessed science teachers’ level of awareness and perception of analogies in secondary school classrooms in Ilorin, Nigeria. The sample comprised 80 science teachers obtained across 34 secondary schools using the convenience sampling technique. A researcher-designed questionnaire titled, “Science Teachers’ Awareness and Perception of Analogies” with a reliability coefficient of 0.82, was used for gathering data. Frequency, percentages, and mean were used to describe the responses, while Analysis of Variance (ANOVA) was used to test the null hypotheses at a 5% level of significance. The findings revealed that the participating science teachers were highly aware of the nature of analogy and had a positively high perception of analogy use. There was no significant difference between science teachers’ awareness and perception of analogy based on their teaching experience. The study concluded that analogies should not be used as the only teaching method even though students learn better with analogies. It was recommended that science teachers take the time to critically assess textbook-recommended analogies to ascertain their relevance to the learners’ immediate experiences.